β2 adrenergic receptor complexes with Ca channels and AMPA receptors mediate localized cAMP signaling - Hell, Johannes (Henry Stewart Talks, 2018)
Introduction to signaling by beta adrenergic receptors and the corresponding regulation of the L-type calcium channel Cav1.2 in brain and heart, Cav1.2 signaling complex in brain, Role of the beta2 adrenergic receptor, Cav1.2, and their association in beta adrenergic signaling in the brain and in synaptic plasticity, Introduction to the signaling complex formed by the beta2 adrenergic receptor with the AMPA-type glutamate receptor (AMPAR), AMPAR signaling complex in brain, Conclusion: formation of a functional unit between the AMPAR and Cav1.2 whose activity is driven by beta2 adrenergic stimulation to augment synaptic strength in a lasting manner